NURSES’ EXPERIENCES IN CARING FOR CHILDREN WITH NEONATAL SEPSIS AT HOLY INNOCENTS CHILDREN’S HOSPITAL IN NYAMITANGA DIVISION, MBARARA DISTRICT. A CROSS SECTIONAL STUDY. - Tumwine, Andrew; Acio, Christine (Student’s Journal of Health Research Africa, 2025)
Background The study aims to assess Nurses’ experiences in caring for children with neonatal sepsis at Holy Innocents Children’s Hospital in Nyamitanga division, Mbarara district. Methodology A qualitative descriptive study design was used. The study involved eight (8) participants, and a purposive sampling method was used. Results All participants were qualified nurses and had completed their basic nursing training successfully. 7 were residing in the hospital staff premises, unlike one. Nurses have a heart of interest, express love for caring for sick children, and show no comparison between their efforts with their payments. They express their challenges in the form of fear, a feeling of worry and threat, find themselves overwhelmed by work on the ward, and express a desire to improve on their already present skills to improve care, especially concerning educating mothers on issues related to home practices on children. Others have weaknesses in controlling their emotions, especially at the workplace, after considering their inputs of care, achieved pediatric experience while caring for children with neonatal sepsis, and have innovative skills to deliver nursing care to these Neonates. The raised spread of infection on the ward and the failure to observe safety precautions have been associated with poor infection control by nurses. Conclusion The experiences of nurses in care were both achievements basing on; devotion, Nurse motivation and achievements whereas challenges were basing on; Inadequacies, Hindrances of care, Cultural involvement, Nurses’ and Mothers’ challenges. Recommendation A level of specialization in pediatric nursing care delivery is required to ensure evidence-based practice. Observations are made through staff appraisals to identify and support incapable nurses with vocational interests in caring for children to go for further studies in pediatric nursing so that evidence-based practice is implemented.